Acceptability of minitablets in soft food. A randomised cross-over study in children - Duncan, Jennifer C.; Page, Rebecca; Clark, Janet; Seddon, Gabrielle; Slater, Joy; Gill, Andrea; Dliso, Silothabo; Ohia, Udeme; Skoutelis, Nikolaos; Wagner-Hattler, Leonie; Baumgartner, Adrian; Sprunk, Angela; et al. (Frontiers in Pharmacology, 2026)
ObjectiveTo evaluate the acceptability of placebo minitablets mixed with different volumes of soft food in children aged 6 months to 7 years.MethodsIn this UK hospital-based, randomised cross-over study, children received placebo minitablets in yoghurt or apple sauce. Those under 1 year received one sample; older children received two. All participants were video recorded taking the samples. Minitablet counts (50–135), and soft food volumes (7.5–30 mL) increased with age. Children aged 1 year + were randomised to “high” or “low” soft food volumes for the first sample; parents chose the soft-food amount for younger children. Swallowability was rated (1–5) by researchers, and palatability by independent reviewers (‘pleasant’, ‘neutral’, or ‘unpleasant’). Palatability and swallowability scores were then combined to assess overall acceptability using the composite endpoint tool. Children aged 4–7 years completed a participant questionnaire.Results100 children were grouped by age: <2 years (G1, n = 16), 2–4 years (G2, n = 37), and ≥5 years (G3, n = 47). Mean age was 4.2 years; 56% were male; 84% were tablet naïve. Youngest was 9 months old. Yoghurt was preferred by 84%. Swallowability was 77% overall, increasing with age (G1: 69%, G2: 73%, G3: 83%). G3 participants consumed more per sample than G1 (at least 80% of minitablets consumed for Samples 1/2, respectively: G3-89%/91% vs. G1-69%/62%). ‘Pleasant’ was the most common palatability rating (48% Sample 1, 52% Sample 2). Some older children reported finding the number of minitablets excessive. Acceptability was 46% (G1), 58% (G2), and 53% (G3), with overall acceptability rated as “high/good” for 54% of participants.ConclusionMinitablets in soft food were generally acceptable for children aged 9 months to 7 years, especially those aged 2–4 years. Swallowability and palatability were good across all age groups. Larger soft-food volumes were often preferred, but both volumes were well tolerated.